2018
DOI: 10.1016/j.cej.2018.05.145
|View full text |Cite
|
Sign up to set email alerts
|

A wet process for oxidation-absorption of nitric oxide by persulfate/calcium peroxide

Abstract: This study develops and evaluates a novel wet method for NO removal using a Na 2 S 2 O 8 /CaO 2 solution. The effects of these two components both and alone in solution, Na 2 S 2 O 8 concentration, CaO 2 concentration, initial pH, reaction temperature, and the concentrations of NO and O 2 on NO removal efficiency were evaluated using a bubbling reactor. The combination of Na 2 S 2 O 8 and CaO 2 had a synergistic effect on NO removal efficiency. NO removal was effected by CaO 2 concentration, reaction temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The feed gas flow rate ranged from 0.05 to 0.25 L/min at a temperature of 323 K. In the present study, the highest absorption efficiency was 94.6% at 0.1 L/min gas flow rate, with a membrane module with 48 fibers, while Wang and Yu (2017) stated the maximum absorption in hydrophobic polypropylene hollow fiber membrane modules with 3000 fibers was ~92% at a 0.05 L/min feed gas flow rate. However, in a wet process of oxidation-absorption in a bubble reactor, the maximum conversion was found to be as high as 94.5% using Na2S2O8 and CaO2 as the oxidants to remove 345 ppm NOx with a feed gas flow rate of 2 L/min (Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The feed gas flow rate ranged from 0.05 to 0.25 L/min at a temperature of 323 K. In the present study, the highest absorption efficiency was 94.6% at 0.1 L/min gas flow rate, with a membrane module with 48 fibers, while Wang and Yu (2017) stated the maximum absorption in hydrophobic polypropylene hollow fiber membrane modules with 3000 fibers was ~92% at a 0.05 L/min feed gas flow rate. However, in a wet process of oxidation-absorption in a bubble reactor, the maximum conversion was found to be as high as 94.5% using Na2S2O8 and CaO2 as the oxidants to remove 345 ppm NOx with a feed gas flow rate of 2 L/min (Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the highest NO removal efficiency of 82% at pH 11. Their subsequent investigation into NO removal using a Na 2 S 2 O 8 /CaO 2 solution discovered that the removal efficiency first increased rapidly and then slowed [7]. Hao et al [8] developed an AOPs system to remove SO 2 and NO simultaneously and achieved an efficiency of 87.8% NO reduction under optimal operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The selective catalytic reduction (SCR) and selective noncatalytic reduction (SNCR) technologies are adopted for NO removal [6], while the wet flue gas desulfurization (WFGD) technology using calcium based solution is adopted for SO 2 removal [7]. In the flue gas, NO accounts for more than 90% of the NO x [8], and is insoluble in aqueous solution. Thereupon, oxidizing insoluble NO to soluble NO 2 before wet scrubbing method is necessary.…”
Section: Introductionmentioning
confidence: 99%